Solid substrate fermentation (SSF) of pineapple waste by aspergillus flavus link 44-1 - Ernie Zuraihah, Rusley (Universiti Malaysia Sarawak, UNIMAS, 2012)
A solid state fermentation of pineapple waste by Aspergillus flavus Link 44-1 was developed for kojic acid production. Kojic acid is an organic acid that is widely used as an ingredient for dermatological products, precursor for flavor enhancer and also as anti-inflammatory drug. In this work, the effects of initial moisture content, pH and incubation time on the cultivation were investigated. The best initial moisture content for kojic acid production via SSF was obtained at 70% (v/w). Maximum production of kojic acid was also attained at pH 3.5 while the optimal range of incubation time for high kojic acid production was seen between 8 and 16 days of incubation. The present study proved the feasibility of pineapple waste as alternative substrate for kojic acid production by A. flavus Link 44-1.